RANCANG BANGUN SET EKSPERIMEN GERAK HARMONIS SEDERHANA MENGGUNAKAN SENSOR PING DAN PHOTODIODA BERBASIS MIKROKONTROLLER - Yulkifli .; Yolanda .; Hatthoahira . (Universitas Halu Oleo, 2017)
Physics experiments have a very important role. The most important thing that must be considered in performing experimental physics experiment is set. The development of digital experiment set not completely perfect, like a set of simple harmonic motion experiments on the spring. This study aims to determine the performance specifications and design specifications set of experiments manufacture simple harmonic motion sensors based on spring ping and photodioda with LCD display and PC. This research was a laboratory experiment. Set the experiment uses Arduino Uno microcontroller which serves to process the output of the sensor and change the sensor output with the expected output display measurement results of the experimental set of simple harmonic motion in the spring using the LCD and PC. The sensor used is a ping sensor yng function calculates the amplitude and photodiode sensors that function to count the number of oscillations in the spring time (ms). Besides this experimental set period has accuracy with accuracy percentage is 96.16% for a single spring arrangement, 96.40% for the composition of the spring series, and 99.25% for the parallel spring arrangement. While the average percentage error obtained is 3.69% for a single spring arrangement, 3.59% for the arrangement of the spring series, 0.74% for the parallel spring arrangement.Keywords : Arduino Uno microcontroller, photodiode sensor, ping sensor